2013
DOI: 10.1159/000343936
|View full text |Cite
|
Sign up to set email alerts
|

Height Deficit and Impairment of the GH/IGF-1 Axis in Patients Treated for Acute Lymphoblastic Leukemia during Childhood

Abstract: Background: Endocrine complications after acute lymphoblastic leukemia (ALL) are common. Methods: Final height, GH/IGF-1 axis, and body mass index were analyzed after 13.7 (7.0–20.7) years from diagnosis in 34 boys aged <12 years at diagnosis and 41 girls <10 years at diagnosis. A modified German BFM-83 ALL protocol included (n = 42) or did not include (n = 33) prophylactic cranial irradiation. In 27 patients, GH after insulin tolerance test, IGF-1, cortisol, free T4 and estradiol/testosterone were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 68 publications
(54 reference statements)
1
9
0
1
Order By: Relevance
“…8 No entanto, o déficit de GH não é a única causa implicada nas alteraç ões do crescimento: a má nutriç ão tão comum nesses doentes, as lesões da coluna vertebral (por RT à espinal medula em tumores como meduloblastomas e ependimomas), a corticoterapia e períodos de imobilizaç ão prolongada, disfunç ão tiroidea associada e eventualmente a presenç a de puberdade precoce são todos fatores que influenciam a estatura final da crianç a. 9 Os efeitos da quimioterapia são controversos: alguns estudos demonstraram que a QT associada à RT espinal agrava as expectativas de estatura na idade adulta. 10,11 A RT espinal provoca muitas vezes uma diminuiç ão irreversí-vel do crescimento vertebral, o que poderá alterar as proporç ões corporais 12 -alteraç ões no quociente entre a estatura em ortostatismo e na posiç ão de sentado.…”
Section: Déficit De Hormônio De Crescimentounclassified
“…8 No entanto, o déficit de GH não é a única causa implicada nas alteraç ões do crescimento: a má nutriç ão tão comum nesses doentes, as lesões da coluna vertebral (por RT à espinal medula em tumores como meduloblastomas e ependimomas), a corticoterapia e períodos de imobilizaç ão prolongada, disfunç ão tiroidea associada e eventualmente a presenç a de puberdade precoce são todos fatores que influenciam a estatura final da crianç a. 9 Os efeitos da quimioterapia são controversos: alguns estudos demonstraram que a QT associada à RT espinal agrava as expectativas de estatura na idade adulta. 10,11 A RT espinal provoca muitas vezes uma diminuiç ão irreversí-vel do crescimento vertebral, o que poderá alterar as proporç ões corporais 12 -alteraç ões no quociente entre a estatura em ortostatismo e na posiç ão de sentado.…”
Section: Déficit De Hormônio De Crescimentounclassified
“…Treatment of ALL during childhood is associated with final height deficit. Young age at diagnosis and radiotherapy are considered the major risk factors [ 6 ]. Moreover, adult survivors of childhood ALL have a four-fold excess risk of mortality from cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…The increased risk of impaired linear growth and obesity/overweight has been largely studied over the past decades to determine whether these adverse outcomes are predictable and potentially reversible. [5][6][7][8][9][10][11][12][14][15][16][17][18][19][20][21][22][23][24] Published results are conflicting and, in some cases, difficult to interpret considering the heterogeneity of therapeutic protocols in use. In recent decades, cranial radiotherapy (CRT) has mostly been replaced by intrathecal chemotherapy as the standard central nervous system prophylaxis and treatment, resulting in less sequelae related to this treatment modality.…”
Section: Introductionmentioning
confidence: 99%
“…Height deficit during treatment is a common finding in children treated for ALL. 5 Many studies further suggest that adult survivors of ALL have long-term impaired growth and decreased final height (FH) [5][6][7] , while others find that FH is not significantly affected by treatment. [8][9][10] Different studies found this effect on linear growth to be more pronounced or only significantly seen in some subgroups such as patients treated with CRT, 7,8,11 females 12 or younger children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation